Electrical resisitivity to detect zones of biogas accumulation in a landfill - Moreira, César Augusto [UNESP]; Munhoz, Thais [UNESP]; Cavallari, Fernanda [UNESP]; Helene, Lívia Portes Innocenti [UNESP] (My University, 2015)
Biogas produced in sanitary landfills consists in a potential source, formed by degradation of organic matter, this gas is constituted by CH4, CO2 and water vapor. Sanitary landfills represent important depository of organic matter with great energetic potential in Brazil, although presently with inexpressive use. Estimates for production or maintenance of productive rates of CH4 represent one of the main difficulties of technical order to the planning and continuity of collection systems for rational consumption of this resource. Electrical resistivity measurements are routinuously used in profiling oil wells for the determination of levels with accumulations of oil and gas, facing the contrast among fluids and rocks. This paper aims to evaluate eventual relationship among biogas flow quantified in surface drains of a waste cell in landfill, with characteristic patterns of in depth electrical resistivity. The integration of Electrical Resistivity Tomography (ERT) lines allowed for the generation of 3D blocks and a clear distinction among zones of high biogas production, quantified in surface drains, with areas of high resistivity in depth. The results suggest the possibility of use of the method in studies to place drains in areas promising to the collection of biogas for energetic generation in sanitary landfill.
Keywords: Electrical resistivity tomography (ERT); Energy; Methane; Organic matter